Effect evaluation of grass roots on mechanical properties of unsaturated coarse-grained soil. (January 2023) - He, Wentao; Ishikawa, Tatsuya; Nguyen, Binh T.
Abstract: The utilization of vegetation to prevent shallow slope failure and erosion has received significant attention in recent years, since it is recognized that vegetation has the mechanical and hydrological strengthening effect on soils. To accurately evaluate the mechanical properties of grassed soil and effect of grass age, grassed soils with grass ages of 2, 4, 6 and 8 months as well as bare soil are cultivated and prepared. Then, considering that grass layer in nature is usually situated above ground water table in the non-saturation state, a sequence of unsaturated triaxial tests are performed for soil specimens with different grass ages and matric suctions. Experimental results reveal that both grass root and matric suction enhance soil shear strength. The peak shear strength and cohesion of grassed soils tend to increase with increasing grass ages or matric suctions. Moreover, it is recognized that compared with grass root, the matric suction causes a more significant reinforcement effect for increasing total cohesion of soil sample. On the other hand, grassed soil has a higher water retention capacity, and under the same matric suction conditions, the soil specimen with older grass age have higher volumetric water content. Furthermore, the measured total cohesion for unsaturated soil is validated by the proposed calculation equation based on Vanapalli model, and the calculated results fit the measured results well. Calculated and experimental results have good agreement showing the proposed equation can properly reflect the increase in the unsaturated mechanical properties of grassed soil.